Hydrodynamic behavior of a canal network under simultaneous supply and demand based operations - Munir, Sarfraz; Schultz, B.; Khan, Abdul Hakeem; Suryadi, F. X.; Gichuki, Francis N. (2007)
The irrigation network of this study consists of three branch canals (the Machai Branch Canal, the Pehure High Level Canal (PHLC) and the Maira Branch Canal) connected to each other in such a way that the Machai Branch and the PHLC feed the Maira Branch Canal for providing a reliable irrigation service. The Machai Branch Canal has limited and erratic discharges and can not fulfill the peak water requirements of the Maira Branch Canal and therefore any deficiency in the supplies to the Maira Branch Canal is automatically compensated by the PHLC. PHLC is an automatic canal and has been equipped with Proportional Integral Derivative (PID) discharge controllers at its head whereas the Machai Branch Canal has fixed supply based operations. The Maira Branch Canal is also an automatically downstream controlled irrigation canal, which is operated according to crop water requirements using Crop Based Irrigation Operations (CBIO) model. Under this scheme of operations the flows remain changing most of the time following the crop water requirements curve. The frequent changes in discharges keep the canal in unsteady state conditions, which affect the functioning of automatic discharge and water level regulation structures. Efficient system operation is a prerequisite for getting better water productivity and the precise understanding of the behavior of the structures and canal's hydrodynamics against such changes is a key for getting effective system operations. In this paper the canal's hydrodynamic behavior and the automatic structures' functioning have been assessed and suggestions have been provided to fine tune the automatic discharge controllers in order to avoid the oscillatory and abrupt hydrodynamic behavior in the canal. The guidelines have been provided for the operation of the secondary system for achieving smooth and sustainable operations of the canals. In addition to this the effects of any discharge variation in the Machai Branch Canal on the automatic discharge controller's behavior also has been assessed.